1996
DOI: 10.1002/(sici)1097-0142(19960615)77:12<2449::aid-cncr6>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cigarette smoking, alcohol, and green tea consumption on the risk of carcinoma of the cardia and distal stomach in Shanghai, China

Abstract: BACKGROUND.The divergent incidence patterns of gastric cardia and distal stom-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 47 publications
4
68
1
Order By: Relevance
“…64,65 Cigarette smoking also has been associated with an increased risk of gastric cancer; however, the absence of control for confounders such as H. pylori infection and fresh produce consumption have hindered the interpretation of many studies. [66][67][68] Obesity may be an important risk factor for gastric cancer of the cardia. 69 Behavioral Risk Factor Surveillance System data indicate that AI/AN populations from all regions have a higher prevalence of obesity than NHW populations.…”
Section: Discussionsupporting
confidence: 93%
“…64,65 Cigarette smoking also has been associated with an increased risk of gastric cancer; however, the absence of control for confounders such as H. pylori infection and fresh produce consumption have hindered the interpretation of many studies. [66][67][68] Obesity may be an important risk factor for gastric cancer of the cardia. 69 Behavioral Risk Factor Surveillance System data indicate that AI/AN populations from all regions have a higher prevalence of obesity than NHW populations.…”
Section: Discussionsupporting
confidence: 93%
“…Smoking Many studies have evaluated the relationship between smoking and risk of stomach cancer. Although some studies obtained negative results, [11][12][13] other studies had positive results, [14][15][16][17][18][19][20][21][22][23][24] several of which showed a linear association between smoking dose and risk of stomach cancer. 10,[25][26][27][28] Among male subjects, smoking dose showed a dosedependent linear association with risk of stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking Although many studies have produced negative results on the relationship between drinking and risk of stomach cancer, 13,16,20,21,25,26,29) some studies have shown positive results. 11,12,19,22,23) A few studies found a linear association. 11,23) In this study, light drinkers showed the lowest risk among both male and female subjects, and heavy drinkers the highest risk among male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these fi ndings, the WCRF/AICR report concluded that high consumption of green tea "possibly" decreases the risk of gastric cancer. More recent case-control studies have also shown a reduction in the risk with green tea intake, most with statistical signifi cance [58][59][60][61].…”
Section: Green Teamentioning
confidence: 99%